Union Structure and Rank and File Revolt : The Israeli Experience - Friedman, Abraham (Relations industrielles / Industrial Relations, 1976)
The high rate of unauthorized strikes in Israel can be attributed to the structural dualism of the largest and most important trade union in Israel— the Histadruth. In structural dualism a reference is made to the incompatibility between the organizational characteristics of the upper echelons of the union, i.e., the trade union department and those of the lower echelons, i.e. the workers' committees. Their goals and relationship with their constituency and political parties are incongruous. While the trade union department adheres to the prescriptions of the national economic policies as put forward by the Labor Alignment party, workers' committees are committed to the short run economic goals of their members at the shop level.